(untitled) (Tanzania Medical Journal, 2025)
Background Thyroid lesions are endemic in Tanzania but poorly documented. Fine needle aspiration cytology (FNAC) is a reliable, cheaper, quicker and easier diagnostic test compared to histopathology but a representative specimen and experience are pre-requisites. Histopathology is available at only a few tertiary health-care centres in Tanzania. Comparable thyroid cytological findings can obviate the need for histopathology where this is not available. Methods This hospital-based retrospective descriptive cross-sectional study was carried out to compare cytology and histopathology in thyroid lesions diagnosis. It included surgical in-patients while pre-operative FNAC was done prior at surgical outpatient (SOPD) clinics between May-2012 and February-2014. Convenience sampling of all patients who underwent FNAC and thyroidectomies with subsequent histopathological evaluation and the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC-2017/18) were used. Results A total of 124 patients were enrolled and age ranged from 12-77 years, mean 40.5±11.66 years, peak-age 31-40 years, and male:female (M:F) ratio=1:7.3. Cytologically, the vast majority (80.6%, n=100/124) were benign, 11.3% (n=14/124) malignant and 8.1% (n=10/124) indeterminate. Comparatively, histopathology showed a similar (82.3%, n=102/124) proportion of benign lesions and a higher (17.7%, n=22/124) proportion of cancers. Furthermore, histopathologically, the commonest (38.1%, n=48/124) benign lesions were colloid goitre and follicular adenoma (19.4%, n=24/124). Nine cases negative for malignancy cytologically, were histologically confirmed as papillary (44.4%, n=4) and follicular carcinoma (55.6%, n=5). Most (92.9%, n=13/14) cases diagnosed as malignancies cytologically, were so confirmed histologically. One patient had papillary carcinoma by FNAC but histologically follicular adenoma. The sensitivity of FNAC was 59.1%, specificity 98.9%, positive predictive value (PPV) 92.9%, negative predictive value (NPV) 91% and accuracy was 91.2%. Conclusion Thyroid lesions at Muhimbili National Hospital (MNH) are comparable to elsewhere. Although FNAC shows low sensitivity it is specific, and accurate as an initial diagnostic test for these lesions which is useful where histopathology is not available.